A severinidade da vida na série Retirantes, de Candido Portinari e em Morte e vida severina, de João Cabral de Melo Neto - Camargo, Nathália de Oliveira (2025)
This dissertation focuses on the Retirantes series (1944), including the paintings Retirantes (1944), Criança Morta (1944), and Enterro na Rede (1944) by Candido Portinari, as well as the Pernambuco nativity play Morte e Vida Severina by João Cabral de Melo Neto, published in 1954. The aim of this analysis is to understand how both artists expressed the relationship between life and death in their works and which resources they used to do so. Additionally, the overall objective of this research is to carry out an analytical-comparative study of the selected works, identifying both similarities and discrepancies between them. The specific objectives are: to analyze the semantic and visual forms in Portinari’s series of paintings in order to understand the figurativization of life based on the key themes he addressed—family, childhood, and labor; and to complement this with an analysis of the figurative isotopies present in the poem, to interpret and relate the text to the paintings. To analyze the selected works, we will draw on several French semiotics scholars, such as Greimas (1973), Greimas and Courtés (2011), Fontanille (2011), Floch (1993), Schwartzmann, Portela, and Dondero (2021), Pietroforte (2020, 2021), and Kress and Van Leeuwen (1996), who argue that the elements created through words in verbal texts can also be created in non-verbal texts, studying semisymbolism and focusing on issues of visuality and figurativization. For the study of Candido Portinari's biography, we will reference works by Callado (2003), Fabris (1990), and Annateresa Fabris and Mariarosaria Fabris (1995); and for the biography of João Cabral de Melo Neto, works by Nunes (1974) and Siqueira (2018). This is a qualitative research project, in which the natural environment is the direct source for data collection, phenomenon interpretation, and meaning attribution. The analysis concludes that the selected works depict a facet of the country where those afflicted by drought are surrounded by death. Portinari paints the suffering of the retirantes as something etched into their skin; João Cabral de Melo Neto's poem is no different—his retirante flees from death, only to encounter it at every turn. The selected paintings display a consistent pattern in coloration, lifeless settings, body deformities, and the meager belongings carried by the retirante families. The poem tells the story of a retirante undertaking an exodus in an attempt to prolong his life, only to find himself encircled by death. These works are in dialogue with each other and exhibit their own nuances—within the poem, the lyrical self ultimately prefers death over continuing his harsh Severino life. This dissertation concludes with the perspective that the analyzed works are social denunciations, each offering, in its own way, reflections on being human and occupying a place in the world.